Acute respiratory distress syndrome and acute lung injury in a trauma population with and without long bone fractures - Larson, Julia L.; Robertson, Henry T.; Grey, Scott F.; Schobel, Seth A.; Potter, Benjamin K.; Elster, Eric A. (Frontiers in Systems Biology, 2023)
Introduction: Trauma is the leading cause of death in persons under the age of 45. Recovery in patients who survive initial trauma are frequently complicated by sequelae of injury that increases susceptibility to infection and inflammation. Uncontrolled inflammation can advance into life-threatening organ failure, including acute respiratory distress syndrome (ARDS). Similarities exist between biomarkers established in the etiology of ARDS and those identified in the acute inflammatory and healing phase of bone fractures. This study investigates the impact of long bone fractures on the development of ARDS where it is hypothesized that patients with long bone fractures would have different biomarker profiles and increased development of lung injury compared to patients without long bone fractures. Methods: This is a retrospective data analysis of patients from an observational data repository from three trauma centers. Trauma patients with and without long bone fractures were matched and analyzed for the presence of known biomarkers of ARDS and for the development of ARDS. Results: There were no differences in overall ARDS development or hospital outcomes, however long bone fracture patients had a 2.35-fold higher hazard ratio of ARDS in the first 10 hospital days. There was a statistically significant increase in the levels of IL-6 in patients with long bone fractures (p = 0.0007). Structural equations modeling demonstrated that IL-6 was positively influenced by long bone fractures and IL-8. Conclusion: The presence of long bone fractures did not result in differences in the overall development of ARDS or hospital outcomes, though was found to have an increased hazard ratio for ARDS development in the first 10 days. Further research is needed to better characterize the relationship between varying cytokine profiles and the development of ARDS in a trauma population.